Building the value system of intellectuals in the curent period - Do, Như Hiến; Nguyen , Thị Mái; Nguyen , Văn Thuyên (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
The strategy of building an advanced Vietnamese culture imbued with national identity requires the participation of all subjects and classes in society, but in which the intellectuals play an important role in national construction and development. The human value system and the Vietnamese value system are two of the core contents of human development and human resource development in the current period. Those value systems directly or indirectly create valuable products and can participate in the global value chains. In order to further promote the strength and potential of the intellectuals, building a value system as the standard and motivation for intellectuals to strive, improve their capacity and qualities to meet the needs of integration and development. In our point of view, the important and core qualities that intellectuals need are creativity, honesty, and independence in practical activities.